Associação do treinamento resistido e aeróbico em pacientes com doença pulmonar crônica - Ambrozin, Alexandre Ricardo Pepe [UNESP]; Paschoal, Anna Maria Joel [UNESP]; Raquel, Doralice Fernanda da Silva [UNESP]; Borges, Juliana Bassalobre Carvalho; Quitério, Robison José [UNESP] (My University, 2013)
Introduction: The pulmonary rehabilitation (PR) is composed of aerobic and resisted exercises that improve the functional capacity to the exercise, life quality and decrease respiratory symptoms in subjects with chronic pulmonary disease. Objective: Assess the effects of a combined PR program in the cardiorespiratory function and peripheral muscle strength in subjects with chronic pulmonary disease. Method: Patients with chronic pulmonary disease were submitted to the PR program, which was developed on 24 sessions of 60 minutes (three times per week). The program was composed of aerobic exercises (two times per week) and resisted exercises (once a week). Before and after the PR the patients were submitted to manovacuometry in order to measure the maximum inspiratory pressure (MIP) and the maximum expiratory pressure (MEP), ventilometry, peek expiratory flow (PEF), six minute walking test (6MWT) and one maximum repetition (1RM). The data are presented in absolute frequency, percentage and mean±standard deviation. The t Student test was used to compare data before and after the PR and the ANOVA test to compare before, after and predicted distances in the 6MWT (p<0.05). Results: Seven patients were part of this study, 85.70% of women, 71.40% with pulmonary emphysema diagnosis. The mean age was 69.43±5.59 years old, the height was 1.61±0.07 m, the mean weight was 66.20±8.40 kg and the body mass index mean was 25.50±2.48 kg/m². From the variables assessed, the MEP increased from 79.71±13.69 to 84.42±12.83 cmH2O (p=0,03), the PEF increase from 255.71±66.3 to 320.00±93.63 l/min (p=0,03) and the distance in the 6MWT from 415.28±47.90 to 483,79±79,77 m (p=0,02). The load in the 1RM test in the reverse peck deck exercise (before - - 17.10±8.10kg; after – 210.40±9.00kg), knee in leg extension machine (before – 17.10±9.50kg; after – 26.40±13.10kg) and hip extensors (right before – 48.60±22.10kg; after – 62.90±19.30kg; and left before – 46.40±20.10kg; after – 62.10±18.20kg) increased significantly (p<0,05). Conclusion: After the PR program there was improvement in the expiratory muscular strength, in the lower limbs strength and in the functional capacity. Besides that, there was a reduction in the airflow obstruction of the subjects with chronic pulmonary disease.

Introdução: A Reabilitação Pulmonar (RP) é constituída por exercícios aeróbicos e resistidos que melhoram a capacidade funcional ao exercício, a qualidade de vida e reduzem sintomas respiratórios em portadores de doença pulmonar crônica. Objetivo: Avaliar os efeitos de um programa de reabilitação pulmonar combinado na função cardiorrespiratória e força muscular periférica de portadores de doença pulmonar crônica. Método: Pacientes portadores de doenças pulmonares crônicas foram submetidos ao programa de RP que foi desenvolvido em 24 sessões com duração de 60 minutos (três vezes por semana). O programa era constituído por exercícios aeróbicos (duas vezes por semana) e resistidos (uma vez por semana). Antes e após a RP os pacientes foram submetidos a manovacuometria para medida da pressão inspiratória máxima (Pimáx) e pressão expiratória máxima (Pemáx), ventilometria, Pico de Fluxo Expiratório (PFE), teste de Caminhada de Seis Minutos (TC6) e teste de uma repetição máxima (1RM). Os dados são apresentados em frequência absoluta, porcentagens e média±desvio-padrão. Foi utilizado o Teste t de Student para comparação dos dados antes e após a RP e Teste de ANOVA para comparação das distâncias do TC6 antes, após e prevista (p<0,05). Resultados: Participaram do estudo 7 pacientes, 85,70% mulheres, 71,40% com diagnostico de enfisema pulmonar. A média da idade foi de 69,43±5,59 anos, da altura foi de 1,61±0,07 m, a média de peso foi de 66,20±8,40 kg e a média do IMC de 25,50±2,48 kg/m². Das variáveis estudadas a Pemáx aumentou de 79,71±13,69 para 84,42±12,83 cmH2O (p=0,03), o PFE aumentou de 255,71±66,3 para 320,00±93,63 l/min (p=0,03) e a distância no TC6 teve aumento de 415,28± 47,90 para 483,79±79,77 m (p=0,02). A carga no teste de 1RM nos exercícios Peck Deck invertido (antes - 17,10±8,10kg; depois - 21,04±9,00kg), mesa extensora (antes - 17,10±9,50kg; depois - 26,40±13,10kg) e extensor de quadril (Direito Antes - 48,60±22,10kg; depois - 62,90±19,30kg; e Esquerdo Antes - 46,40±20,10kg; depois - 62,10±18,20kg) aumentaram significativamente (p<0,05). Conclusão: Após o programa de RP houve melhora na força muscular expiratória, na força de membros inferiores e na capacidade funcional, e diminuição na obstrução ao fluxo aéreo dos portadores de doença pulmonar crônica.
Association in the resistance and aerobic training in patients with disease chronic pulmonary